Structural Deterioration and Failure of the Laminated Wooden Roof of a Covered Swimming Pool - Javier Pinilla-Melo; Nelson Flores-Medina; Luis Javier Sánchez-Aparicio; Jose Ramón Aira-Zunzunegui (Buildings)
A swimming pool in Corrales de Buelna (Cantabria) was demolished in March 2017 due to the loss of mechanical performance of the laminated timber structure. The relevant deterioration was caused by rotting of the wood and corrosion of the metal connecting elements. The structure featured a barrel vault with five large tri-articulated arches enclosed on the sides by inclined facades formed by toral rafters and purlins. The corresponding diagnostic process involved data collection and structural assessments to verify the structure’s bearing capacity and serviceability. Data collection was carried out in December 2015 and consisted of a thermal camera inspection to determine the points of moisture accumulation and sampling openings, conduct environmental and wood hygrothermal measurements, and measure cross-sectional losses and deformations of the structural elements. Verification of the load-bearing capacity was carried out using matrix calculation structure software for both the original and deteriorated structure. The diagnosis indicated that the damage was caused by leaks in the joints of the aluminum composite roof panels and by the insufficient load-bearing capacity of the structure. The severity of the damage compromised the mechanical strength and stability of the building, leading to a recommendation that the use of the facilities be immediately discontinued. The degree of deterioration left the structure unrecoverable, making it very difficult to apply reinforcement measures. These factors led to the structure’s demolition to prevent its collapse.